Neutrophil extracellular traps formation and clearance is enhanced in fever and attenuated in hypothermia - Janko, Jakub; Bečka, Emil; Kmeťová, Katarína; Hudecová, Letícia; Konečná, Barbora; Celec, Peter; Bajaj-Elliott, Mona; Pastorek, Michal (Frontiers in Immunology, 2023)
Fever and hypothermia represent two opposite strategies for fighting systemic inflammation. Fever results in immune activation; hypothermia is associated with energy conservation. Systemic Inflammatory Response Syndrome (SIRS) remains a significant cause of mortality worldwide. SIRS can lead to a broad spectrum of clinical symptoms but importantly, patients can develop fever or hypothermia. During infection, polymorphonuclear cells (PMNs) such as neutrophils prevent pathogen dissemination through the formation of neutrophil extracellular traps (NETs) that ensnare and kill bacteria. However, when dysregulated, NETs also promote host tissue damage. Herein, we tested the hypothesis that temperature modulates NETs homeostasis in response to infection and inflammation. NETs formation was studied in response to infectious (Escherichia coli, Staphylococcus aureus) and sterile (mitochondria) agents. When compared to body temperature (37°C), NETs formation increased at 40°C; interestingly, the response was stunted at 35°C and 42°C. While CD16+ CD49d+ PMNs represent a small proportion of the neutrophil population, they formed ~45-85% of NETs irrespective of temperature. Temperature increased formyl peptide receptor 1 (FPR1) expression to a differential extent in CD16+ CD49d- vs. CD49d+ PMNSs, suggesting further complexity to neutrophil function in hypo/hyperthermic conditions. The capacity of NETs to induce Toll-like receptor 9 (TLR9)-mediated NF-κB activation was found to be temperature independent. Interestingly, NET degradation was enhanced at higher temperatures, which corresponded with greater plasma DNase activity in response to temperature increase. Collectively, our observations indicate that NETs formation and clearance are enhanced at 40°C whilst temperatures of 35°C and 42°C attenuate this response. Targeting PMN-driven immunity may represent new venues for intervention in pathological inflammation.